Rechtsbehelfe gegen Verzögerungen in ZPO- und FamFG-Verfahren - Boczek, Lukas (Universitätsverlag Göttingen, 2023)
Legal proceedings need time. On the other hand, the duration of proceedings can have an impact on their outcome and major consequences for the parties. Nevertheless, German procedural law provides parties with little recourses to speed up proceedings in which undue delays have occurred. For proceedings that have an impact on the litigants' family life, this violates article 13 of the ECHR, the European Court of Human Rights decided in its Kuppinger II judgment. As a consequence, legal remedies for the expedition of proceedings have been introduced into the German Act on Proceedings in Family Matters and in Matters of Non-contentious Jurisdiction. This dissertation examines whether the new remedies fulfil the requirements of the ECHR and whether the Basic Law and the Convention require similar remedies in civil proceedings, other family proceedings and in proceedings in matters of non-contentious jurisdiction.